Technical Review on Endoscopic Ultrasound-Guided Hepaticogastrostomy - Singh, Vivek Kumar; Dhir, Vinay (Journal of Digestive Endoscopy, 2025)
Endoscopic ultrasound-guided biliary drainage (EUS BD) over the last decade has become accepted as a standard technique for BD in routine clinical practice. EUS-guided hepaticogastrostomy (HGS) has been adopted worldwide for various benign and malignant pathologies following failed endoscopic transpapillary cholangiopancreatography or inaccessible papilla due to duodenal stenosis or surgically altered anatomy. With increasing acceptance of EUS HGS, its efficacy and safety has now been tested for primary BD. Since its wider adoption, there is rising focus on improving EUS imaging and developing more dedicated accessories and stents, which cater to EUS HGS. With the aim of making the procedure safe and effective while reducing complication rates and making it more accessible, this review focuses on technical aspects of EUS HGS with tips and tricks that we use in our practice.
Keywords: endoscopic ultrasound; EUS-guided biliary drainage; EUS HGS